The Calculated Ratio of the Gas Flow in a Countercurrent Cyclone Dust Concentrator; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Vasilevsky M. V. Mikhail Viktorovich; Razva A. S. Aleksandr Sergeevich; Pleschko A. Alissa; Kadurkin I. Ivan (2016, 2016)
Title screen